Preventing posterior sagittal anoplasty 'cripples' in areas with limited medical resources: A few modifications to surgical approach in anorectal malformations - Claudio Olivieri; Kibreab Belay; Riccardo Coletta; Giuseppe Retrosi; Philippe Molle; Alessandro Calisti (Wolters Kluwer Medknow Publications, 2012)
Background: Anorectal malformations (ARM) are the most common neonatal emergencies in Sub-Saharan Africa countries. Late presentation, lack of pediatric facilities and trained paediatric surgeons influence the outcome of these patients. This study reports a 5-year of experience in the management of ARM at the Orotta Referral Hospital in Asmara (Eritrea) and proposes some modified surgical approaches to minimize the risk of complications and the length of hospital stay. Materials and Methods: We reviewed the records of 38 patients with ARM observed between September 2006 and April 2011. Since 2009 a modification of original posterior sagittal anorectoplasty (PSARP) was introduced, consisting in a long rectal stump (3 cms) closed and left at the perineal level, to be trimmed after two weeks. This avoided mucous spillage on the wound and prevented contamination. Post-operative course and outcome were evalued in the two group of patients divided according the type of surgical technique (Group A: Standard PSARP; Group B: Modified PSARP). Results: There were 21 boys and 17 girls aged 4 days to 9 years (median age 182 days). Of the 38 patients, 2 infants died before surgery and 3 refused preliminary colostomy. Previously confectioned colostomies often required revision or redoing due to severe prolapse or malposition. When possible, primary sigmoid colostomy was performed. There were 15 patients in Group A and 18 in Group B. Wound infection or disruption were recorded in 7 cases (46%) in Group A and in 2 (11%) in Group B. Late complications were related to anal stenosis, which required long term dilatations. Three cases needed a PSARP redo (2 in Group A, 1 Group B). Conclusions: We believe that our simple modification of original PSARP technique could be of help lowering post-operative complications rate and reducing hospital stay. Family compliance is mandatory for long-term surgical success. A relevant time must be spent in training to stoma care and post-operative anal dilatation.